2004
DOI: 10.1111/j.1365-2591.2004.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of varying concentrations of sodium hypochlorite on the endodontic microorganisms Actinomyces israelii, A. naeslundii, Candida albicans and Enterococcus faecalis

Abstract: The published association of E. faecalis with refractory endodontic infection may result, at least partially, from high resistance of this species to NaOCl. This does not appear to be the case with A. naeslundii or C. albicans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
147
0
23

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(181 citation statements)
references
References 37 publications
11
147
0
23
Order By: Relevance
“…Furthermore, there is evidence that hypochlorite is not effective against all pathogenic bacteria specifically Enterococcus faecalis which is associated with recalcitrant canals. 14 Further complications of conventional disinfecting agents are toxicity and microbial resistance [15][16][17] since most which have effective bactericidal activity are used at concentrations where normal tissue toxicity is becoming a significant factor. This can lead to adverse tissue reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is evidence that hypochlorite is not effective against all pathogenic bacteria specifically Enterococcus faecalis which is associated with recalcitrant canals. 14 Further complications of conventional disinfecting agents are toxicity and microbial resistance [15][16][17] since most which have effective bactericidal activity are used at concentrations where normal tissue toxicity is becoming a significant factor. This can lead to adverse tissue reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Vianna et al (22) demonstrated that the time required by 1% NaOCl to eliminate suspensions of E. faecalis, S. aureus, and C. albicans was 20 minutes. Whereas Radcliffe et al (23) verified that the same concentration of irrigant required 10 minutes to promote negative cultures of suspensions of E. faecalis. However, Retamozo et al (24) observed that 1.3% NaOCl was not able to disinfect dentin cylinders contaminated with E. faecalis even after 40 minutes of irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, it is relatively ineffective against Enterococcus faecalis, a root canal microorganism. 15 Sodium hypochlorite also has a high surface tension which prevents deeper penetration of the irrigant into dentinal tubules. 16 Increasing the temperature of the solution and the time that it is in contact with tissues in the root canal can increase cellular destruction.…”
Section: Root Canal Irrigantsmentioning
confidence: 99%